(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article discusses the system of forming a sense of national pride in students by means of ethno-pedagogical values, and special emphasis is placed on the issues of educating our young people to be mature in all aspects and raising the sense of patriotism in today's dangerous times.В данной статье рассматривается система формирования у учащихся чувства национальной гордости средствами этнопедагогических ценностей, при этом особый акцент делается на вопросах воспитания у нашей молодежи зрелого во всех отношениях и воспитания чувства патриотизма в современных опасных условиях. раз.